A MODEL OF UNIVERSITY EXAMINATION MONITORING SYSTEM - Henry, Ogbu Nwani (IJRDO -Journal of Computer Science Engineering, 2016)
This work takes into consideration the system of examination invigilation in Nigeria universities. Over the years, the extent of students’ malpractice in examinations and the resultant effects when confronted by invigilators or university security agents have been on the increase and devastating. According to Ejiogu (2001), general moral decadence and the high premium placed on achievement and certificates by Nigerians has in recent times spawned examination fraud. There arose the need for an examination automated monitoring system that will handle this societal menace. This journal therefore x-rays the exact way students take examination and tries to portray each student’s grade with his academic capabilities. It is a system of examination conduction that monitors the examination arena (halls) and stores live-fed videoed scenario for future screening and use. The system is designed and developed with webcams at the examination halls to capture the student’s face, posture and movement at every moment during examination. The